2019
DOI: 10.3389/fpsyg.2019.02248
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Adolescents’ Stress and Internet Addiction: A Mediated-Moderation Model

Abstract: This cross-sectional study explored the impact of stress, social anxiety, and social class on Internet addiction among adolescents. The subjects—1,634 middle school students—were investigated using the Chinese Perceived Stress Scale (CPSS), the Social Anxiety Scale for Adolescents (SAS-A) Chinese Short Form, the Chinese Internet Addiction Scale (CIAS), and the Questionnaire of Family Social-economic Status. The results show that 12% of the adolescents investigated showed signs of Internet addiction. With the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
44
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 51 publications
(44 reference statements)
5
44
0
5
Order By: Relevance
“…Specifically, a significant gender difference emerged, as showed in previous studies (Cao et al, 2011;Barke et al, 2012;Kuss et al, 2013). As showed in a study by Feng et al (2019), we have found a significant grade difference.…”
Section: Discussionsupporting
confidence: 84%
“…Specifically, a significant gender difference emerged, as showed in previous studies (Cao et al, 2011;Barke et al, 2012;Kuss et al, 2013). As showed in a study by Feng et al (2019), we have found a significant grade difference.…”
Section: Discussionsupporting
confidence: 84%
“…Earlier studies have revealed a positive relationship between perceived stress and Internet addiction among various age groups. 6,27,28 Mild and moderate internet addictions in our study were positively associated with a higher level of perceived stress. This finding was consistent with a similar study among resident doctors of a tertiary care hospital of north India.…”
Section: Discussionsupporting
confidence: 46%
“…Stress was considered to be a common risk factor of both chemical addictions [e.g., drug dependence; ( 42 )] and behavioral addictions [e.g., excessive smartphone use; ( 43 )]. Earlier studies found perceived daily stress to be positively related to addictive Facebook use ( 18 ) and Internet addiction ( 44 ). The current study adds value to the existing literature by measuring objective pandemic-related stress rather than subjectively perceived stress.…”
Section: Discussionmentioning
confidence: 99%